2014
DOI: 10.2474/trol.9.10
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion Behaviour of Biodiesel ^|^mdash; A Review

Abstract: Biodiesel serves as the best alternative candidate to diesel fuel for diesel engines as a result of its ability to function as substitute to meet with the rising energy demand. Biodiesel is considered more environmentally friendly than fossil fuel because it is made from renewable resources and has lower emissions. This paper focuses on the tribocorrosion behaviour of biodiesel followed by development of tribocorrosion model with the aim of understanding the combined effects of tribology and corrosion (synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…occurs during sliding of the mating surfaces. Oxidation of the moving motor component reacts with biodiesel, which facilitates wear and friction [6]. When the behavior of metals used in automobiles is examined with biodiesel, it is observed that stainless steel is more resistant than copper and aluminum [7].…”
Section: Effect Of Biodiesel On Automotive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…occurs during sliding of the mating surfaces. Oxidation of the moving motor component reacts with biodiesel, which facilitates wear and friction [6]. When the behavior of metals used in automobiles is examined with biodiesel, it is observed that stainless steel is more resistant than copper and aluminum [7].…”
Section: Effect Of Biodiesel On Automotive Materialsmentioning
confidence: 99%
“…The accuracy of the path followed and the method of test directly affects the accuracy of the result. Many different test methods and laboratory setups have been suggested in previous studies [6,11]. However, in order to achieve more accurate results, the innovations to wear models can contribute to the work in this area.…”
Section: Wear Modelmentioning
confidence: 99%
“…where K [1,20] is the specific wear rate in mm 3 /N•m; V is the wear volume of material loss in mm 3 ; L is normal load in N and d is the total sliding distance in m; T [21] is the total material loss rate in mm/year; W c and C w are the total material loss due to mechanical wear and the total material loss due to corrosion, respectively; W 0 is the mechanical wear in absence of corrosion calculated from wear tests at cathodic potential; C 0 is the corrosion material loss rate in the absence of wear, which is normally treated as being negligible for passive metals and alloys; ∆W c is the change in wear rate due to corrosion in mm/year, and ∆C w is the change in corrosion rate due to wear in mm/year. Thus, T in tribocorrosion can be expressed as in Equation 5.…”
Section: Tribocorrosion Testingmentioning
confidence: 99%
“…where T, W 0 [22] is the wear rate in mm/year; SA is the surface area of the wear track; t is the test time; k is a constant (3.27 × 10 −3 ) in mm•g/µA.cm.year; i ωt is the flowing current from wear track during abrasion in µA/cm 2 ; M is the equivalent weight (22.55 g/mol for CrFeCoNi and 28.68 g/mol for CrFeCoNiSn) which was calculated according to the ASTM G102-89 standard [19], and ρ is the density (8.20 g/cm 3 for CrFeCoNi and 8.44 g/cm 3 for CrFeCoNiSn) measured using MS104S/01 NewClassic MF density balance equipment (Mettler Toledo, Greifensee, Switzerland). The driving force for this material loss is the galvanic couple that forms between the depassivated surface (wear track) and the still passivated one (the rest of the surface).…”
Section: Tribocorrosion Testingmentioning
confidence: 99%
See 1 more Smart Citation